Culturally adaptive storytelling intervention versus didactic intervention to improve hypertension control in Vietnam: a cluster-randomized controlled feasibility trial - Hoa L. Nguyen; Jeroan J. Allison; Duc A. Ha; Germán Chiriboga; Ha N. Ly; Hanh T. Tran; Cuong K. Nguyen; Diem M. Dang; Ngoc T. Phan; Nguyen C. Vu; Quang P. Nguyen; Robert J. Goldberg (Pilot and Feasibility Studies, 2017)
Abstract Background Vietnam is experiencing an epidemiologic transition with an increased prevalence of non-communicable diseases. Novel, large-scale, effective, and sustainable interventions to control hypertension in Vietnam are needed. We report the results of a cluster-randomized feasibility trial at 3 months follow-up conducted in Hung Yen province, Vietnam, designed to evaluate the feasibility and acceptability of two community-based interventions to improve hypertension control: a “storytelling” intervention, “We Talk about Our Hypertension,” and a didactic intervention. Methods The storytelling intervention included stories about strategies for coping with hypertension, with patients speaking in their own words, and didactic content about the importance of healthy lifestyle behaviors including salt reduction and exercise. The didactic intervention included only didactic content. The storytelling intervention was delivered by two DVDs at 3-month intervals; the didactic intervention included only one installment. The trial was conducted in four communes, equally randomized to the two interventions. Results The mean age of the 160 study patients was 66 years, and 54% were men. Most participants described both interventions as understandable, informative, and motivational. Between baseline and 3 months, mean systolic blood pressure declined by 8.2 mmHg (95% CI 4.1–12.2) in the storytelling group and by 5.5 mmHg (95% CI 1.4–9.5) in the didactic group. The storytelling group also reported a significant increase in hypertension medication adherence. Conclusions Both interventions were well accepted in several rural communities and were shown to be potentially effective in lowering blood pressure. A large-scale randomized trial is needed to compare the effectiveness of the two interventions in controlling hypertension. Trial registration ClinicalTrials.gov, NCT02483780